LITERASI DIGITAL: ANALISIS IMPLEMENTASINYA PADA PENDIDIKAN SEKOLAH DASAR SEBAGAI INDIKATOR PENCAPAIAN SDGs 2030 - Ilham Permana; Jajang Riana; Ichsan Fauzi Rachman (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Digital literacy is the ability of individuals to integrate writing, reading and thinking skills to process and understand information about technology in an ethical and accountable manner. Digital literacy education must be provided since elementary school education because students tend to be unstable and easily influenced by the environment so that they are at risk of being negatively affected by technology. Currently, the Government has integrated digital literacy content in the formal education curriculum at the elementary school education level. This study aims to examine the level of digital literacy skills of primary school students, the effectiveness of government efforts to improve digital literacy skills of primary school students, and analyse the possibility of achieving the 2030 SDGs Quality Education target. The research method used is a qualitative method of literature study and field study with a descriptive approach. The results show that digital literacy skills of primary school students have developed thanks to the implementation of digital literacy learning through ICT special subjects and digital literacy content in general subjects, indicating that digital literacy learning practices in formal education have been effective and the quality education target in SDGs 2030 is very likely to be achieved in the future.